Sleep and Tibialis Anterior Muscle Activity in Mice With Mild Hypoxia and Iron Deficiency: Implications for the Restless Legs Syndrome - Lo Martire, Viviana; Alvente, Sara; Bastianini, Stefano; Berteotti, Chiara; Valli, Alice; Manconi, Mauro; Zoccoli, Giovanna; Silvani, Alessandro (Frontiers in Physiology, 2018)
Restless legs syndrome (RLS) is a neurological disorder that entails an urge to move with a circadian pattern during the evening/night. RLS may be accompanied by decreased sleep time and increased occurrence of periodic leg movements during sleep (PLMS), which involve bursts of tibialis anterior (TA) muscle electromyogram (EMG). Mild hypoxia and non-anemic iron deficiency, a highly prevalent nutritional deficiency, are relatively unexplored factors in RLS pathophysiology. We tested whether mice exposed to mild hypoxia, alone or in combination with non-anemic iron deficiency, show decreased sleep time particularly in the light (rest) period and increased occurrence of TA EMG phasic events similar to human PLMS. Female C57BL/6J mice were fed diets with low or normal iron for 6 months from weaning and instrumented with electrodes to record the electroencephalogram and the EMG of both TA muscles. Mice were recorded in a whole-body plethysmograph while breathing a normoxic or mildly hypoxic (15% O2) gas mixture for 48 hours. Hypoxia increased minute ventilation during sleep. The low-iron diet decreased liver and serum iron, leaving blood hemoglobin and brainstem iron levels unaffected. Hypoxia, either alone or in combination with non-anemic iron deficiency, decreased non-rapid-eye-movement (non-REM) sleep time, but this occurred irrespective of the light/dark period and was not associated with increased occurrence of TA EMG events during non-REM sleep. These results do not support the hypothesis that mild hypoxia is sufficient to cause signs of RLS, either alone or in combination with non-anemic iron deficiency, pointing to the necessity of further susceptibility factors.